Exploring innovation ecosystem from the perspective of sustainability: Towards a conceptual framework - Zheng Liu; Victoria Stephens (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
With technology advancement, industrial revolution 4.0, businesses nowadays are in competition in terms of product, service and business model innovation. Meanwhile, the emergent socio-ecological crisis is making it increasingly important to identify the impact of business on environment and the society. To date, much literature has explored how sustainability might be achieved through firms' internal research and development, and supply chain collaboration. However, issues such as how different stakeholders including customers, partners, government, and universities can be involved, forming innovation ecosystem in a sustainable way is under-explored. This paper aims to provide connection between innovation and sustainability, through literature review and exploratory case studies. A conceptual framework is generated starting from firm/intra-firm level, to supply chain/inter-firm level, and towards ecosystem level. With emerging themes of innovation from sustainability perspective proposed, the framework can be enriched and validated through future empirical studies.
Keywords: 650; innovation; innovation ecosystem; sustainability; sustainable innovation